Lower extremity muscle strength equation of older adults assessed by Five Time Sit to Stand Test (FTSST) - Weerasak Tapanya; Noppharath Sangkarit; Patchareeya Amput; Saisunee Konsanit (World Scientific Publishing, 2024)
Background: The decline in lower limb muscle strength, one of the risk factors for falling in the older adults, puts older persons at an increased risk of falling. The assessment of the lower limb muscle strength is very important. Objective: The purpose of this study was to construct the equation for predicting knee extensor muscle strength based on demographic data and the results of the Five-Time Sit-to-Stand Test (FTSST). Methods: A total of 121 healthy elders (mean age [Formula: see text]) were asked to complete the FTSST and submit the demographic information. By using a stationary push-pull dynamometer, the knee extensor strength of each participant was assessed. The multiple regression analysis was used to explore knee extensor strength prediction equation. Results: The findings demonstrated that the knee extensor strength equation was developed using variables obtained from gender, weight, and time to complete the FTSST. The equation was found to have a high correlation ([Formula: see text]) and 70.1% estimation power. Its formula was as follows: Knee extensor [Formula: see text] (gender; [Formula: see text] or [Formula: see text])[Formula: see text][Formula: see text][Formula: see text]0.189 (weight)[Formula: see text]−[Formula: see text]2.617 (time to complete the FTSST). However, there was an estimating error in this equation of 4.72[Formula: see text]kg. Conclusion: The determining factors influencing knee extensor strength, which can be utilized to estimate the strength in elderly individuals, are demographic variables including gender, weight, and the time taken to complete the FTSST.